Effect of Brewing Water on the Antioxidant Capacity of Green Tea Infusion with DPPH Assay. (4th January 2022) - Cao, Qing-Qing; Fu, Yan-Qing; Zhang, Cheng-Bin; Zhu, Yan; Yin, Jun-Feng; Granato, Daniel; Putnik, Predrag; Xu, Yong-Quan
Abstract : Brewing water plays a crucial role in flavor and potential healthy functions of tea infusion. In this study, seven water samples with different physicochemical properties were selected to brew green tea. Results showed that the brewing water with higher minerals level and pH value would reduce the yield of catechins in tea infusion, which in turn caused the decrease of antioxidant activity to a large extent. Besides, it was found that EGCG, as a major contributor to the antioxidant activity of green tea infusion, was influenced differently by different metal ions, among which Ca 2+ /Mg 2+ could enhance the antioxidant activity of EGCG solutions with different concentration through synergistic effect, particularly Ca 2+, and the effect was more markable at a higher EGCG concentration. These results offered theoretical direction to the selection of tea brewing water for consumers and gave a new sight to the effects of metal ions on the antioxidant capacity of EGCG.